2009
DOI: 10.1007/s00417-009-1109-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgically induced astigmatism in combined phacoemulsification and vitrectomy; 23-gauge transconjunctival sutureless vitrectomy versus 20-gauge standard vitrectomy

Abstract: Combined phacoemulsification and pars plana vitrectomy (23-gauge and 20-gauge) could induce significant SIA at postoperative week 1, and decrease over 3 months. However, 23-gauge TSV showed less SIA and early stabilization compared to the 20-gauge standard vitrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 25 publications
2
32
0
1
Order By: Relevance
“…Several studies reported the safety and effectiveness of the 23-gauge MIVS. [7][8][9][10][11] However, there have been questions regarding the self-sealing characteristics and postoperative hypotony in some of the cases. 8,12,13 Previously localized conjunctival and episcleral pigmentation after 20-gauge conventional vitrectomy has been considered owing to a reaction to the sutures used to close the sclerotomy site.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported the safety and effectiveness of the 23-gauge MIVS. [7][8][9][10][11] However, there have been questions regarding the self-sealing characteristics and postoperative hypotony in some of the cases. 8,12,13 Previously localized conjunctival and episcleral pigmentation after 20-gauge conventional vitrectomy has been considered owing to a reaction to the sutures used to close the sclerotomy site.…”
Section: Introductionmentioning
confidence: 99%
“…In the toric IOL group, the IOL cylinder power and alignment axis were calculated using a web-based toric IOL calculator program (available at: http://www.acrysoftoriccalculator.com) taking into account the keratometry readings and mandatory data input on the position of the incision and the SIA by superior incision (0.30 D), which was measured from our previous investigation. 7 The manufacturer's information shows the SN60T3, SN60T4, and …”
Section: Patients and Study Designmentioning
confidence: 99%
“…[4][5][6] Recently, 23-gauge microincisional vitrectomy surgery (MIVS) had less surgically induced astigmatism (SIA) compared with 20-gauge vitrectomy. 7 However, it could not correct pre-existing corneal astigmatism.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of sutureless small-gauge vitrectomy include techni cal simplicity, less traumatic conjunctival and scleral manipulation, shorter operative durations, less severe postoperative pain, and faster postoperative visual recovery (2,3) . Several studies have demonstrated corneal changes induced by standard 20-G vitrectomy; however, few studies have investigated (2)(3)(4)(5) . This study aimed to evaluate and compare corneal topographic changes following pars plana vitrectomy (PPV) using 20-, 23-, and 25-G systems.…”
Section: Introductionmentioning
confidence: 99%